Unification of Tarekat in Indonesia: A Critical Review - Ziaulhaq Hidayat (Hikmah, 2022)
This study aims to conduct a critical review of a dissertation on the unification of tarekat in Indonesia. To understand how critical review works, a summary will be made of the dissertation that is used as the object of study. The critical review work step is carried out by trying to present an overview of the dissertation that will be critically reviewed to provide an overview of the material being analyzed. Content analysis is a characteristic of this study, with which opinion interpretations are carried out. The findings of the study explain that this dissertation explains that the Sufistic thoughts of Ahmad Khatib Sambas are considered unique compared to other Sufis, because Ahmad Khatib Sambas succeeded in combining two large orders, namely the Qadiriyah and Naqsyabandiyah Orders which then taught them separately. Apart from that, this tarekat has a quite prominent spirit of activism, as evidenced by several resistance movements against colonialism sponsored by followers of the Qadiriyah and Naqsyabandiyah Tarekat. The results of the critical review show that this research has not succeeded in answering what is at the core of the research problem. The research findings presented are too broad, so they do not focus on the main discussion. In addition, this study also failed to present novelty from previous studies.